2015
DOI: 10.1155/2015/329057
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability in Shift Workers: Responses to Orthostatism and Relationships with Anthropometry, Body Composition, and Blood Pressure

Abstract: In order to investigate the response of heart rate variability (HRV) components to postural change and their association with cardiovascular risk factors in shift workers, a cross-sectional study with 438 Brazilian males rotating shift workers was done. Anthropometric, body composition, and clinical measures were collected. Electrocardiogram was recorded for 3 minutes, in the supine and orthostatic position, and HRV components were extracted. Descriptive analyses showed that mean values of body mass index, wai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
6
0
5
Order By: Relevance
“…Abreviaturas: VFC: variabilidade da frequência cardíaca; iRR: intervalo da FC; DP: desvio padrão; FC: frequência cardíaca; rMSSD: raiz quadrada da média das diferenças sucessivas ao quadrado entre R-R adjacentes; RRtri índice: índice triangular de VFC; BF: banda de baixa frequência; AF: banda de alta frequência; nu: unidades normalizadas; BF/AF: relação entre as bandas BF e AF; SD1 e SD2: parâmetros de plotagem Poincare; MASR: manobra de arritmia sinusal respiratória. (Continua) inferiores, promovido pela carga ortostática que, por sua vez, provoca aumento do estímulo simpático e elevação da pressão arterial 7 . Este comportamento foi verificado nos estudos de Jiang et al 16 e Mahananto et al 17 , realizados com sujeitos depressivos e saudáveis respectivamente, onde durante a mudança postural de sedestação para ortostase, houve uma maior ativação da modulação simpática e atenuação vagal.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Abreviaturas: VFC: variabilidade da frequência cardíaca; iRR: intervalo da FC; DP: desvio padrão; FC: frequência cardíaca; rMSSD: raiz quadrada da média das diferenças sucessivas ao quadrado entre R-R adjacentes; RRtri índice: índice triangular de VFC; BF: banda de baixa frequência; AF: banda de alta frequência; nu: unidades normalizadas; BF/AF: relação entre as bandas BF e AF; SD1 e SD2: parâmetros de plotagem Poincare; MASR: manobra de arritmia sinusal respiratória. (Continua) inferiores, promovido pela carga ortostática que, por sua vez, provoca aumento do estímulo simpático e elevação da pressão arterial 7 . Este comportamento foi verificado nos estudos de Jiang et al 16 e Mahananto et al 17 , realizados com sujeitos depressivos e saudáveis respectivamente, onde durante a mudança postural de sedestação para ortostase, houve uma maior ativação da modulação simpática e atenuação vagal.…”
Section: Resultsunclassified
“…A análise da VFC reflete a interação dos sistemas simpático e parassimpático ao sistema cardiovascular, através de terminações aferentes e eferentes no miocárdio, nodo sinusal e nodo atrioventricular 6 . Esta interação é de suma importância no aumento ou redução do desempenho cardíaco em diferentes circunstâncias 7 , sendo estes influenciados pelos barorreceptores, quimiorreceptores, receptores atriais e ventriculares, além de modificações no sistema respiratório, vasomotor e termorregulador 8 . No entanto, as respostas do controle autonômico frente às modificações do posicionamento do corpo no espaço e durante a Manobra de Arritmia Sinusal Respiratória (MASR), particularmente em amputados de membros inferiores, precisam ser esclarecidas.…”
Section: Introductionunclassified
“…Finally, lower BMI was associated with higher SD1 recovery, regardless of the gender of the participants. Some authors showed associations between an increase in the anthropometric measures and a decrease in the vagal components of HRV, during the resting period [ 15 , 18 ]. In the present study, this result was replicated and expanded, thus showing that an increase in anthropometric measures might indeed affect adversely the vagal flexibility during the test.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, epidemiological studies have shown a relationship between cardiovascular risk factors and anthropometric variables—increased body mass, body mass index (BMI), waist circumference (WC), hip circumference (HC), and waist-hip ratio (WHR). A study from our group showed that age, WC, visceral fat, and systolic blood pressure are negatively associated with HRV vagal components [ 15 ]. Anthropometric changes were associated with low fitness levels, low levels of vagal activity, or high levels of stress, all of which are related to cardiac morbidity [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation